Supply Chain Resilience and Firm Performance in Cameroon - Ndode, Bony (International Journal of Business Strategies, 2024)
Purpose: The aim of the study was to assess the supply chain resilience and firm performance in Cameroon. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study showed a strong positive correlation between a company's ability to effectively manage disruptions and its overall performance. Supply chain resilience refers to an organization's capacity to anticipate, respond to, and recover from disruptions in its supply chain. Studies indicate that firms with resilient supply chains are better equipped to navigate challenges such as natural disasters, geopolitical unrest, and economic fluctuations. Key findings suggest that resilient supply chains contribute to improved financial performance, operational efficiency, customer satisfaction, and competitive advantage. Companies that invest in building resilience through strategies like redundancy in sourcing, flexible manufacturing processes, and robust risk management systems tend to experience fewer disruptions and recover more quickly when faced with unforeseen events. Furthermore, resilient supply chains enable firms to maintain continuity in product availability, meet customer demands during turbulent times, and adapt swiftly to changing market conditions. This adaptability not only enhances overall performance but also strengthens relationships with stakeholders, including suppliers, customers, and investors. Implications to Theory, Practice and Policy: Resource-based view (RBV), contingency theory and dynamic capabilities theory may be used to anchor future studies on assessing the supply chain resilience and firm performance in Cameroon. Organizations can enhance their supply chain resilience and performance by implementing practical recommendations derived from current research. Advocating for industry-wide standards, interoperability protocols, and regulatory frameworks is essential to support the widespread adoption of emerging technologies in supply chain operations.